Nanopartículas poliméricas baseadas em comonômeros catiônicos para liberação de praziquantel - Alves, Jéssica Bentes (2018)
Schistosomiasis is one of the most neglected diseases in the world in which millions of people are infected, but the young children are the most affected by this disease. The treatment is performed with the drug praziquantel (PZQ), which has poorly soluble and a characteristic bitter taste. The PZQ is mainly available in the form of tablets, but there are no specific pediatric formulations. Polymer nanoparticles (PPNs) have great potential as drug carriers, because of their chemical resistance and high rate encapsulation. The main objective of this work is to encapsulate the PZQ in nanoparticles of poly (methyl methacrylate) copolymerized with cationic comonomers (DEAEMA (diethylaminoethyl methacrylate) and DMAEMA (dimethylaminoethyl methacrylate)) by miniemulsion polymerization. PPNs were obtained through different compositions, evaluating the use of a polar and nonpolar initiator and an anionic and cationic surfactant. The PPNs were characterized evaluating the properties of the copolymers, drug incorporation and drug-polymer interaction. Also, PZQ release tests were conducted to analyze the feasibility of the final product. Nanoparticles were obtained with conversion around of 100% and the encapsulation efficiency was greater than 98%. The results obtained show that the different comonomers together with the drug content significantly affect the stability and performance of PPNs.